2011
DOI: 10.2108/zsj.28.882
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y in Tiger Puffer (Takifugu rubripes): Distribution, Cloning, Characterization, and mRNA Expression Responses to Prandial Condition

Abstract: Neuropeptide tyrosine (NPY) is a potent orexigenic neuropeptide implicated in feeding regulation in rodents. However, the involvement of NPY in feeding behavior has not well been studied in fish. Therefore, we investigated the role of NPY in food intake using a tiger puffer (Takifugu rubripes) model. We observed the distribution of NPY-like immunoreactivity in the brain. Neuronal cell bodies containing NPY were located in the telencephalon, hypothalamus, mesencephalon, and medulla oblongata, and their nerve fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 48 publications
9
23
0
Order By: Relevance
“…Both RT-PCR and in situ hybridization analyses demonstrated that TpNPY was expressed in the metencephalon, which is consistent with previous studies of the cerebellum of carp [30]. However, NPY mRNA was not detected in the cerebellum of tiger puffer [18] or Atlantic cod [21]. Here, we show that TpNPY is expressed in the pituitary gland, which is in agreement with previous reports in other fish species [9,15,32].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Both RT-PCR and in situ hybridization analyses demonstrated that TpNPY was expressed in the metencephalon, which is consistent with previous studies of the cerebellum of carp [30]. However, NPY mRNA was not detected in the cerebellum of tiger puffer [18] or Atlantic cod [21]. Here, we show that TpNPY is expressed in the pituitary gland, which is in agreement with previous reports in other fish species [9,15,32].…”
Section: Discussionsupporting
confidence: 93%
“…Although the prepro-TpNPY peptide exhibits a variable degree of similarity with the NPY peptides of other species, a maximal similarity was observed in mature peptide regions among teleosts. Moreover, the mature TpNPY sequence is completely identical to the NPY sequence of other fish, such as black porgy, mandarin fish, Nile tilapia, sea bass [5], Chinese perch [27] and tiger puffer [18]. The mature TpNPY peptide exhibited conserved aa residues, including Pro 2 , Pro 5 , Pro 8 , Tyr 20 and Tyr 27 , which are known to be crucial for the maintenance of the peptide conformation of the NPY family [6].…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations